Design and study of valveless piezoelectric pump with streamlined chamber fishtail-type bluff body - Xiaochao Tian; Zhenming Wang; Kai Yang; Yang Bai; Yingyu Dai; Defeng Niu; Zhicheng Zhong (AIP Advances)
To enhance the flow rate of a valveless piezoelectric pump and improve the stability of the fluid flow, a valveless piezoelectric pump with a streamlined chamber fishtail-type bluff body (VPFB) is proposed. Compared with the traditional conical chamber, the streamlined chamber reduces the generation of eddy currents and energy loss, increasing the output efficiency of the piezoelectric pump. On the other hand, the fishtail-type bluff body increases the resistance when the fluid flows in the reverse direction, reducing the backflow. First, the three-dimensional model of VPFB is designed and theoretically analyzed based on the piezoelectric inverse effect and fluid dynamics to derive the expression of the relationship affecting the flow rate of the piezoelectric pump. Second, the finite element method is used to analyze the flow field and pressure of VPFB. Finally, the prototype is made, and the experimental platform is built to test the output performance of VPFB. The experimental results show that the output flow rate of VPFB is 27.1 ml/min when the driving voltage is 150 V and the driving frequency is 50 Hz, which is 8% higher compared with the traditional triangular bluff body piezoelectric pump. The fishtail-type bluff body is optimized with parameters, and the maximum output flow rate of the designed piezoelectric pump is 44.18 ml/min when the height is 2 mm. When changing its length to 4 mm, the pump output flow rate can reach 45.51 ml/min. The streamlined chamber proposed in this paper provides a new idea in the research field of valveless piezoelectric pumps.